"As long as you live under my roof… ". (April 2015) - Warnick, Bryan R.
Why should we respect the rights of parents to control the education of their children? The author probes this question through a thorough philosophical examination of the nature of the parent-child relationship. The labor of parenting, which is performed for the sake of the intimate relationships, the author says, creates a specific right: the right to invite children into a life that the parents value and treasure, often the life that they themselves lead. This 'right to invite' allows parents the opportunity to lived shared lives – lives of common beliefs and commitments – with their children. While it does not guarantee that children will accept the invitation, the right to invite allows parents the opportunity to expose children to their own way of life.